2015
DOI: 10.1039/c4nr05015k
|View full text |Cite
|
Sign up to set email alerts
|

Nanotextured stainless steel for improved corrosion resistance and biological response in coronary stenting

Abstract: Nanosurface engineering of metallic substrates for improved cellular response is a persistent theme in biomaterials research. The need to improve the long term prognosis of commercially available stents has led us to adopt a 'polymer-free' approach which is cost effective and industrially scalable. In this study, 316L stainless steel substrates were surface modified by hydrothermal treatment in alkaline pH, with and without the addition of a chromium precursor, to generate a well adherent uniform nanotopograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 43 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…In this paper, we present a novel approach to nanotexture the stent surface to concurrently enable enhanced endothelialization and reduced smooth muscle cell proliferation. Previous works by our group as well as others have shown the beneficial effects of nano‐topographical modifications of metals, mainly titanium, in regulating cellular behavior . Our research demonstrated stable and uniform nanotextured titania surface on metallic Ti through a facile hydrothermal processing technique that exhibited excellent vascular cell response and hemocompatibility in vitro .…”
Section: Introductionmentioning
confidence: 90%
“…In this paper, we present a novel approach to nanotexture the stent surface to concurrently enable enhanced endothelialization and reduced smooth muscle cell proliferation. Previous works by our group as well as others have shown the beneficial effects of nano‐topographical modifications of metals, mainly titanium, in regulating cellular behavior . Our research demonstrated stable and uniform nanotextured titania surface on metallic Ti through a facile hydrothermal processing technique that exhibited excellent vascular cell response and hemocompatibility in vitro .…”
Section: Introductionmentioning
confidence: 90%
“…14 Our results also correspond to other studies evaluating the effects of nanostructure on in vitro hemolysis, in which low roughness nanoscale topographies (of titanium and 316 L stainless steel) did not induce hemolysis under static and/or dynamic conditions. 26,27 Although the NCD coatings in this study did not demonstrate hemolytic effects, some studies have reported hemolysis as well as RBC penetration and an effect on RBC oxygenation function in blood exposed to discrete nanodiamond particles. Adverse responses to nanodiamond particles should be considered for NCD coatings due to the potential of nanoparticulate wear debris.…”
Section: Discussionmentioning
confidence: 54%
“…These results are consistent with the literature in which carbon‐based coatings exhibited no hemolytic response . Our results also correspond to other studies evaluating the effects of nanostructure on in vitro hemolysis, in which low roughness nanoscale topographies (of titanium and 316 L stainless steel) did not induce hemolysis under static and/or dynamic conditions …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations